Analisis Pembelajaran Berdiferensiasi pada Mata Pelajaran Aqidah Akhlak di MAS Simatorkis Kecamatan Rao Selatan - Juliana Pasaribu; Ulva Rahmi; Muhiddinur Kamal; Januar Januar (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
This study is prompted by challenges in implementing differentiated learning, including the time and preparation demands on teachers, reduced student engagement without effective communication ofthe approach, insufficient teacher training in designing and managing differentiated learning, and resource constraints, such as limited facilities for Aqidah Akhlak-aligned materials. The focus is on class X students, and the research employs a qualitative approach, collecting data through observation, interviews with school officials and teachers, and documentation at MAS Simatorkis, South Rao District. Results indicate successful differentiation in Aqidah Akhlak learning, fostering increased student participation, active engagement, and application of religious values in daily life. Key findings stress the importance of diverse learning methods, relevant materials, and tailored attention to individual student needs, considering varying levels of understanding.